Targeting Store-Operated Calcium Entry Regulates the Inflammation-Induced Proliferation and Migration of Breast Cancer Cells - Mohammed Alqinyah; Abdullah S. Alhamed; Hajar O. Alnefaie; Mohammad M. Algahtani; Amira M. Badr; Abdullah M. Albogami; Mohamed Mohany; Yasseen A. Alassmrry; Adel F. Alghaith; Hussain N. Alhamami; Khalid Alhazzani; Ahmed Z. Alanazi; et al. (Biomedicines, 2023)
Persistent challenges complicating the treatment of breast cancer remain, despite some recent undeniable successes. Sufficient evidence currently exists demonstrating the crucial role of inflammation, characterized by the enhanced activation of Toll-like receptor 4 (TLR4) and the COX-2/PGE2 pathway, in the migration and proliferation of breast cancer cells. Interestingly, the store-operated calcium entry (SOCE) pathway was shown to be essential for the TLR4 activity and COX-2 expression in immune cells such as macrophages and microglia. However, whether SOCE influences inflammatory signaling and the inflammation-induced proliferation and migration of breast cancer cells is still unknown. Thus, the current study intended to delineate the role of SOCE in the TLR4-induced inflammation, migration, and proliferation of breast cancer cells. To this end, MDA-MB-231 breast cancer cells were treated with lipopolysaccharide (LPS) to activate TLR4, BTP2 to inhibit SOCE, and Thapsigargin to induce SOCE. Following these treatments, several experiments were conducted to evaluate the proliferation and migration rates of the MDA-MB-231 cells and the expression of several inflammatory and oncogenic genes, including COX-2, PGE2, IL-6, IL-8, and VEGF. Different techniques were used to achieve the aims of this study, including qRT-PCR, Western blotting, ELISA, MTT, and wound healing assays. This study shows that SOCE inhibition using BTP2 suppressed the LPS-induced migration and proliferation of breast cancer cells. Additionally, treatment with LPS caused approximately six- and three-fold increases in COX-2 mRNA and protein expression, respectively, compared to the controls. The LPS-induced elevations in the COX-2 mRNA and protein levels were suppressed by BTP2 to the control levels. In addition to its effect on COX-2, BTP2 also suppressed the LPS-induced productions of PGE2, IL-6, IL-8, and VEGF. Conversely, SOCE induction using Thapsigargin enhanced the LPS-induced inflammation, migration, and proliferation of breast cancer cells. Collectively, these results provide evidence for the potentially important role of SOCE in inflammation-induced breast cancer progression processes. Thus, we argue that the current study may provide novel targets for designing new therapeutic approaches for the treatment of breast cancer.